Effect of Counseling Packages on The Diet of Pregnant Women With Chronic Energy Deficiency - Risqi Dewi Aisyah; Suparni Suparni; Fitriyani Fitriyani (Universitas STRADA Indonesia, 2020)
Pregnancy is the most important of nutrition of each woman's lifetime. Proper nutrient intake during this period has an important role in fetal development. This type of research is a quasy experiment that researchers measure variables before a counseling package. The design of this study is Observational Analytics. The sample in this study used non probability sampling te type namely 30 pregnant women who experienced chronic energy deficiency. Data collection using cheklis food recal. The data analysis technique to be used with T-Test. The results of the studya value of p=0.001 (<0.05) can be concluded that Ho was rejected and Ha accepted which means there is a very significant difference between the diet of respondents before and after the provision of counseling packages. It is expected for midwives to provide more in-depth counseling and continuous monitoring to pregnant women who are chronically deficient. Keywords : pregnancy, chronic energy deficiency, counseling